Structural and magnetic properties of chemically synthesized Fe doped ZnO - Kumar, Shalendra; Kim, Y. J.; Koo, B. H.; Sharma, S. K.; Vargas, J. M.; Knobel, M.; Gautam, S.; Chae, K. H.; Kim, D. K.; Kim, Y. K.; Lee, C. G. (AMER INST PHYSICS, 2009)
We report on the synthesis of Fe-doped ZnO with nominal composition of Zn0.99Fe0.01O by using a coprecipitation method. X-ray diffraction and selective area electron diffraction studies reveal a single phase wurtzite crystal structure without any secondary phase. Field emission transmission electron microscopy measurements infer that Zn0.99Fe0.01O have nanorod-type microstructures. Magnetic hysteresis measurement performed at different temperatures show that Zn0.99Fe0.01O exhibits a weak ferromagnetic behavior at room temperature. A detailed investigation of the electronic and local structure using O K-, Fe L-3,L-2 near edge x-ray absorption fine structure suggests that Fe is substituting Zn in ZnO matrix and is in Fe3+ state. (C) 2009 American Institute of Physics. [DOI: 10.1063/1.3073933]
Keywords: FERROMAGNETISM